The integration of statistical process control and engineering process control in reactor system: article - Abdul Khar, Nur ‘Izzati Simaa’; Abd Karim, Siti Fatma (2017)
Integration of Statistical Process Control (SPC) and Engineering Process Control (EPC) in the system for the purposed to monitoring and adjusting the disturbance and fault that cause variation to the system or process. Batch reactor have a bigger issue in controlling the temperature also lack of on-line monitoring and controlling worst the problem. The main goal of this research paper is to present the integration of SPC and EPC in the batch reactor. The EPC adjustment have been applied apart from assignable cause and fault detection using SPC. The SPC mechanism act as trigger to EPC have been approached in control scheme. The different type of SPC tools: Shewhart chart, Exponential Moving Average (EMWA) chart and Cumulative Sum (CUSUM) chart have been approach to monitor the process. The CUSUM and EMWA chart is more effective than Shewhart because can quickly detecting mean shift that are small relative to measurement system.